4H-pyranylidene-based small push-pull chromophores: Synthesis, structure, electronic properties and photovoltaic evaluation. (July 2020) - Tejeda-Orusco, Víctor; Blais, Martin; Cabanetos, Clément; Blanchard, Philippe; Andreu, Raquel; Franco, Santiago; Orduna, Jesús; Diosdado, Beatriz E.
Abstract: The synthesis and electrochemical and optical characterizations of four new 4 H -pyranylidene-based push-pull molecules are reported herein as well as their evaluation as donor materials for organic photovoltaics. Studied systems exhibit good absorption properties and appropriate LUMO levels for a photoinduced electron transfer to C60 . Bilayer organic solar cells fabricated from these new donors and C60 as the acceptor gave photocurrent however with low power conversion efficiencies. As shown by X-ray diffraction and theoretical calculations, titled molecules present a twisted structure which may prevent the formation of suitable π-π contacts between adjacent molecules hence explaining their low photovoltaic performance. Highlights: Small push-pull molecules featuring a 4H-pyranylidene moiety as donor fragment are reported. New molecules present very good optical properties and well-adjusted LUMO levels compared to C60 . A clear photovoltaic effect is observed and low power conversion efficiencies due to weak π-π intermolecular interactions.